THE FACTORS AFFECTING OF THE SYRIAN IMMIGRANTS TO BECOME ENTREPRENEUR: THE CASE OF HATAY PROVINCE (Third Sector Social Economic Review, 2018)
The concept of migration, which is defined as the work of individuals moving from one country to another country for economic, social or political reasons, has many economic and social effects both in origin countries and host countries. The entrepreneurship activities of immigrants is one of the most important factors that influence these effects. In this connection, it is called immigrant entrepreneurship that settle into a different country and start an enterprise apart from their homeland or citizenship country. Immigrant entrepreneurship is the period in which entrepreneurial activities are carried out in the country of immigration, and that the economic and social value is revealed by the immigrants. As a result of internal disturbance since 2011, more than 3.5 million refugees have come to Turkey from Syria. Hatay province is one of the regions where these refugees live intensely. In Hatay province, 457.106 Syrian immigrants live according to the figures of the year 2017. Some of these immigrants are trying to provide their livelihood by carrying out even if entrepreneurship activities in small scale. In this context, the factors affecting of the Syrian immigrants to become entrepreneur have been examined by the logit model in the study. According to survey findings on 400 Syrian immigrants, it has been concluded that the entrepreneurs' marital status, professional experience, business experience, their monthly income and the life expectancy in Hatay are effective in the Syrian immigrants to become entrepreneur.
Keywords: Immigration; Immigrant; Immigrant Entrepreneurship; Syrian Immigrants; Logit Model